Effects of repetitive transcranial magnetic stimulation on learning and memory cognitive function in rats with vascular cognitive impairment and its neural induction mechanism - Jiati Wang; Huan Gao (BMC Neuroscience)
Abstract Background The treatment of vascular cognitive impairment (VCI) is challenging, and its neurological mechanisms are not yet fully understood. Repetitive transcranial magnetic stimulation (rTMS) offers a new non-invasive treatment approach. Methods One hundred male SD rats were grouped: intervention group (IG), model group (MG), sham group (SG), and control group (CG), to prepare the rat model of VCI. The Morris water maze (MWM) test was conducted, and oxidative stress (OS) markers, neurotrophic factors, apoptosis factors, and the amplitude of postsynaptic potential (PSP) in the hippocampus of rats were measured. Results Post-intervention, IG’s escape latency was lower than MG but higher than SG and CG. IG’s hippocampal malondialdehyde (MDA) content, Bax, and Caspase-3 (Cas-3) were lower than MG but higher than SG and CG, while the tendency was opposite for Bcl-2 expression and the content of glutathione (GSH) and superoxide dismutase (SOD). IG’s brain-derived neurotrophic factor (BDNF), glial cell line-derived neurotrophic factor (GDNF), and N-methyl-d-aspartate receptor 1 (NMDAR1) in the hippocampus were higher than MG but lower than SG and CG; The changes in the amplitude of PSP in the hippocampal region of IG at 10, 30, and 60 min were all higher than those in MG but lower than those in SG and CG (P < 0.05). Conclusion Low-frequency rTMS visibly improved the learning and memory abilities of VCI rats and reduced OS levels.